Bridging Clinical And Administrative Healthcare: Systematic Review Of Collaborative Models Between Medical Laboratory Technicians, Nursing Staff And Health Information Technicians In Saudi Vision 2030 Healthcare Reforms (The Review of Diabetic Studies, 2024)
The Saudi Vision 2030 healthcare reforms emphasize digital transformation and integrated care delivery, necessitating enhanced collaboration between clinical nursing staff and health information technicians. This systematic review synthesizes existing literature on collaborative models, barriers, and facilitators affecting interprofessional partnerships in technology-enabled healthcare environments, with specific consideration of the Saudi Arabian context. A comprehensive search identified 38 peer-reviewed articles addressing nursing-health information technology collaborations, interprofessional teamwork models, and healthcare digitalization initiatives. Findings reveal that successful collaboration requires clearly defined roles, shared governance structures, integrated training programs, and technological infrastructure supporting bidirectional communication. Barriers include professional silos, inadequate informatics competencies among nursing staff, workflow disruptions, and resistance to organizational change. Facilitators encompass interprofessional education, collaborative decision-making frameworks, administrative support, and alignment with national healthcare transformation goals. The review highlights significant gaps in empirical research specifically examining nursing-health information technician partnerships within the Saudi Vision 2030 context. Recommendations emphasize developing competency frameworks, establishing formal collaborative structures, and conducting implementation research to evaluate partnership models in Saudi healthcare settings. These findings inform strategic planning for healthcare workforce development and technology integration aligned with national reform objectives.